2018
DOI: 10.1111/hsc.12628
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m on the train and I can't stop it': Western Canadians' reactions to prediabetes and the role of self-compassion

Abstract: Prediabetes, a condition characterised by impaired glucose regulation, is on the rise worldwide. This condition puts people at risk for cardiovascular disease, and 50% of people with prediabetes will develop type 2 diabetes (T2D). People with prediabetes can reduce their risk of developing T2D through lifestyle changes such as regular physical activity and healthy eating. However, the experience of health risks can be associated with negative reactions that can undermine people's ability to self-regulate the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 40 publications
(79 reference statements)
0
32
0
Order By: Relevance
“…Exploring the dimensions of achieving and maintaining lifestyle change At trial, first recruit: > 40 years, Caucasians with BMI > 25 and IGT diagnosed based on two OGTTs n = 15 F = 7 M = 8 Age range: 47–74 Semi-structured interviews, content analysis, framework approach Empirical phenomenology approach Not described Setting: A study nested from the European Diabetes Prevention Study (EDIPS); intervention was individual motivational interviewing (three-month interval) aiming to reduce total food energy and fat intake and increasing activity. Exploring experiences of the participants 3–5 years after Area for lifestyle change (intervention): To promote exercise and dietary changes Strachan et al, 2018, Canada [ 48 ] Exploring how people from a small Canadian city diagnosed with prediabetes react emotionally to their diagnosis Between 18 and 65 years old, diagnosed with prediabetes according to the ADA (2016): HbA1c = 5.7%-6.4% ( n = 20) or ADA risk-questionnaire indicating increased risk (> 5 = 1) within the past year n = 21* F = 18 M = 3 Age range: 47–65 years *A subsample of participants from a larger study on diabetes prevention. The subsample participants were selected by random Semi-structured interviews, inductive thematic analysis (Braun and Clarke) Not described Setting: The study was part of a larger project where people with prediabetes participated in a 3‐week community‐based lifestyle intervention in Western Canada, “Small Steps for Big Changes Program (SSB)”.…”
Section: Resultsmentioning
confidence: 99%
“…Exploring the dimensions of achieving and maintaining lifestyle change At trial, first recruit: > 40 years, Caucasians with BMI > 25 and IGT diagnosed based on two OGTTs n = 15 F = 7 M = 8 Age range: 47–74 Semi-structured interviews, content analysis, framework approach Empirical phenomenology approach Not described Setting: A study nested from the European Diabetes Prevention Study (EDIPS); intervention was individual motivational interviewing (three-month interval) aiming to reduce total food energy and fat intake and increasing activity. Exploring experiences of the participants 3–5 years after Area for lifestyle change (intervention): To promote exercise and dietary changes Strachan et al, 2018, Canada [ 48 ] Exploring how people from a small Canadian city diagnosed with prediabetes react emotionally to their diagnosis Between 18 and 65 years old, diagnosed with prediabetes according to the ADA (2016): HbA1c = 5.7%-6.4% ( n = 20) or ADA risk-questionnaire indicating increased risk (> 5 = 1) within the past year n = 21* F = 18 M = 3 Age range: 47–65 years *A subsample of participants from a larger study on diabetes prevention. The subsample participants were selected by random Semi-structured interviews, inductive thematic analysis (Braun and Clarke) Not described Setting: The study was part of a larger project where people with prediabetes participated in a 3‐week community‐based lifestyle intervention in Western Canada, “Small Steps for Big Changes Program (SSB)”.…”
Section: Resultsmentioning
confidence: 99%
“…This metaphor suggests a perception that T2D is an abyss—place of irreversible loss. In another study, participants viewed prediabetes as ‘being on a train that they could not stop’ 37 . Strachan and colleagues found that for many, it was inevitable that the progression of T2D will occur, regardless of health support since the risk factors associated with prediabetes were primarily embedded in the participant's everyday lives.…”
Section: Discussionmentioning
confidence: 99%
“…To relate the awareness of the present moment and the way in which compassionate and critical attitudes towards the self can be managed as possible emotion regulation strategies,56 101 the evaluation of the dispositional mindfulness and self-compassion levels will be pursued as mechanistic variables of the programme through application of the widely used Five Facet Mindfulness Questionnaire (FFMQ), the Mindful Eating Scale (MES) and the Self-Compassion Scale (SCS). Mindfulness is a way of self-regulating attention to focus it on the present moment experience with an attitude of curiosity, openness and acceptance of bodily sensations, thoughts and emotions 102.…”
Section: Methodsmentioning
confidence: 99%